2007
DOI: 10.1111/j.1365-2958.2007.05780.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the TrmB‐like protein, PF0124, a TGM‐recognizing global transcriptional regulator of the hyperthermophilic archaeon Pyrococcus furiosus

Abstract: SummaryThe characterization of the transcriptional regulator TrmBL1 of the hyperthermophilic archaeon Pyrococcus furiosus, homologous to TrmB (transcriptional regulator of the maltose system), was studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
54
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 33 publications
(48 reference statements)
4
54
1
Order By: Relevance
“…Depending on its position within the respective promoter, Tgr binds to it, acting as an activator when present upstream of BRE/TATA box of genes encoding gluconeogenic proteins but as a repressor when positioned downstream of the BRE/ TATA box of genes encoding glycolytic genes. TrmBL1 of P. furiosus showing 67% sequence identity to Tgr and exhibits the same function as Tgr [3].…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Depending on its position within the respective promoter, Tgr binds to it, acting as an activator when present upstream of BRE/TATA box of genes encoding gluconeogenic proteins but as a repressor when positioned downstream of the BRE/ TATA box of genes encoding glycolytic genes. TrmBL1 of P. furiosus showing 67% sequence identity to Tgr and exhibits the same function as Tgr [3].…”
Section: Introductionmentioning
confidence: 94%
“…Nevertheless, when tested by band shift analysis and run-off transcription assays, it was found that TrmBL2 was able to recognize the MD promoter but no obvious pattern with respect to other TGM-containing promoters could be detected, neither could a specific DNA sequence motif for TrmBL2 be identified [3,5].…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations